Trypanocidal Activity of Antitumor Antibiotics and Other Metabolic Inhibitors - Williamson, J. (1978)
A microtest has been devised for the rapid preliminary assay in vitro of the effect of over 100 drugs and inhibitors on African trypanosomes (Trypanosoma brucei and T. rhodesiense). Parasite motility and infectivity for mice are indexes, respectively, of respiration and glycolysis and of cell division; trypanocidal titers based on these indexes can show primary metabolic areas of drug attack. Various specific inhibitors have also been tested to detect metabolic sites which might be therapeutically vulnerable. RNA synthesis inhibitors are highly active (adenine nucleosides, daunorubicin, doxorubicin, chromomycin, actinomycin D, mitomycin C); the activity of the nucleoside cordycepin was increased in vitro and in vivo by an adenosine deaminase inhibitor. In view of the polyanionic nature of the trypanocide suramin, a series of polyanions was tested; several showed activity but only poly-d-glutamic acid was active in vivo. Among various miscellaneous inhibitors, quercetin, disulfiram, and the Ca-complexing agents arsenazo I and III showed marked activity, the latter exclusively on the arsenical-resistant T. brucei. The implications of these results for combination chemotherapy and depot prophylaxis (with polyanions) are indicated.